Prospective monitoring of chronic myeloid leukemia patients from the time of TKI discontinuation: the fate of peripheral blood CD26+ leukemia stem cells - Paola Pacelli; Adele Santoni; Anna Sicuranza; Elisabetta Abruzzese; Valentina Giai; Monica Crugnola; Mario Annunziata; Sara Galimberti; Alessandra Iurlo; Luigiana Luciano; Federica Sorà; Carmen Fava; et al. (Frontiers Media S.A., 2023)
Introduction: In chronic myeloid leukemia (CML), about half of the patients achieving a deep and stable molecular response with tyrosine kinase inhibitors (TKIs) may discontinue TKI treatment without disease recurrence. As such, treatment-free remission (TFR) has become an ambitious goal of treatment. Given the evidence that deepness and duration of molecular response are necessary but not sufficient requisites for a successful TFR, additional biological criteria are needed to identify CML patients suitable for efficacious discontinuation. Leukemia stem cells (LSCs) are supposed to be the reservoir of the disease. Previously, we demonstrated that residual circulating CD34+/CD38-/CD26+ LSCs were still detectable in a consistent number of CML patients during TFR.Methods: CML LSCs could be easily identified by flow-cytometry as they express the CD34+/CD38-/CD26+ phenotype. In this study, we explored the role of these cells and their correlation with molecular response in a cohort of 109 consecutive chronic phase CML patients prospectively monitored from the time of TKI discontinuation.Results: After a median observation time of 33 months from TKI discontinuation, 38/109 (35%) patients failed TFR after a median time of 4 months, while 71/109 (65%) patients are still in TFR. At TKI discontinuation, peripheral blood CD26+LSCs were undetectable in 48/109 (44%) patients and detectable in 61/109 (56%). No statistically significant correlation between detectable/undetectable CD26+LSCs and the rate of TFR loss was found (p = 0.616). The incidence of TFR loss based on the type of TKI treatment was statistically significant for imatinib treatment compared to that of nilotinib (p = 0.039). Exploring the behavior of CD26+LSCs during TFR, we observed fluctuating values that were very variable between patients, and they were not predictive of TFR loss.Discussion: Up to date, our results confirm that CD26+LSCs are detectable at the time of TKI discontinuation and during TFR. Moreover, at least for the observation median time of the study, the persistence of "fluctuating" values of residual CD26+LSCs does not hamper the possibility to maintain a stable TFR. On the contrary, even patients discontinuing TKI with undetectable CD26+LSCs could undergo TFR loss. Our results suggest that factors other than residual LSCs "burden" playing an active role in controlling disease recurrence. Additional studies evaluating CD26+LSCs' ability to modulate the immune system and their interaction in CML patients with very long stable TFR are ongoing.